2018
DOI: 10.3382/ps/pey253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature fluctuation on embryonic development and mortality, and hatchability of broiler hatching eggs

Abstract: The effects of temperature fluctuation during 7 d of storage on stage of blastoderm development, embryonic mortality, and hatchability of broiler hatching eggs were studied. Hatching eggs from 2 commercial flocks of Ross 308 broiler breeders at 27 and 50 wk of age, respectively, were randomly assigned to replicate chambers with either a constant temperature (Constant) of 18°C or a temperature that fluctuated (Fluctuated) over a 40 min period 3 times daily (0900 h, 1300 h, and 1700 h) between 18°C and 21°C. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…In fact, prolonged storage resulted in a higher early and middle mortality than shorter storage, but this effect was more pronounced in older breeders. Okur et al [ 52 ] and Özlü et al [ 53 ] also noted a higher embryonic mortality rate with stored eggs from older breeders (55 vs. 32 weeks and 27 vs. 50 weeks, respectively). Tona et al [ 18 ] attributed the higher reduction of hatchability of prolonged stored eggs of older breeders to the lower quality of the albumen at oviposition compared to younger breeders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, prolonged storage resulted in a higher early and middle mortality than shorter storage, but this effect was more pronounced in older breeders. Okur et al [ 52 ] and Özlü et al [ 53 ] also noted a higher embryonic mortality rate with stored eggs from older breeders (55 vs. 32 weeks and 27 vs. 50 weeks, respectively). Tona et al [ 18 ] attributed the higher reduction of hatchability of prolonged stored eggs of older breeders to the lower quality of the albumen at oviposition compared to younger breeders.…”
Section: Discussionmentioning
confidence: 99%
“…Nicholson et al ( 2013 ) documented that in SPIDES treatment, the highest outcomes showed whenever the shell temperature was above > 32°C for 2–5 h and maintained at 35 °C for 2–3 h. Özlü et al ( 2021a ) and Reijrink et al ( 2009 ) hypothesized that fetus is in the pre-gastrula phase of growth at egg collection, and SPIDES treatment with extended storage periods is most advantageous. Özlü et al ( 2018 ), Özlü et al ( 2021a ), and Pokhrel et al ( 2018 ) they noted that newly laid eggs from younger breeder flocks exhibit earlier embryonic mortalities than eggs from older breeder flocks.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nutrition can affect embryonic development and progeny growth since all nutrients required for embryo development are acquired by nutrient transfer from the breeders ( Richards et al, 2010 ; Özlü et al, 2018 ; Emamverdi et al, 2019 ). More trace minerals could be transferred from breeders to progeny chicks when breeders were fed highly bioavailable source of minerals, MMHAC.…”
Section: Discussionmentioning
confidence: 99%